NSAIDs-hypersensitivity often induces a blended reaction pattern involving multiple organs. Issue 1 (December 2018) - Doña, Inmaculada; Barrionuevo, Esther; Salas, María; Laguna, José; Agúndez, José; García-Martín, Elena; Bogas, Gádor; Perkins, James; Cornejo-García, José; Torres, María
Abstract Non-steroidal anti-inflammatory drugs (NSAIDs)-induced hypersensitivity reactions are classified by the European Network on Drug Allergy (ENDA) as either cross-reactive or selective. The former is the most frequent type and includes patients with exclusively respiratory symptoms (NSAIDs-exacerbated respiratory disease, NERD) or exclusively cutaneous symptoms: NSAIDs-induced urticaria/angioedema (NIUA); and NSAIDs-exacerbated cutaneous disease (NECD). However, although not reflected in the current classification scheme (ENDA), in clinical practice a combination of both skin and respiratory symptoms or even other organs such as gastrointestinal tract symptoms (mixed or blended reactions) is frequently observed. This entity has not been sufficiently characterised. Our aim was to clinically characterize blended reactions to NSAIDs, comparing their clinical features with NERD and NIUA. We evaluated patients with symptoms suggestive of hypersensitivity to NSAIDs who attended the Allergy Unit of the Regional University Hospital of Malaga (Malaga, Spain) between 2008 and 2015. We included 880 patients confirmed as cross-reactive based on clinical history, positive nasal provocation test with lysine acetylsalicylate (NPT-LASA), and/or positive drug provocation test (DPT) with acetylsalicylic acid (ASA), who were classified as blended (261; 29.6%), NERD (108; 12.3%) or NIUA (511; 58.1%). We compared symptoms, drugs, underlying diseases and diagnostic methods within and between groups. Among blended patients the most common sub-group comprised those developing urticaria/angioedema plus rhinitis/asthma (n = 138), who had a higher percentage of underlying rhinitis (p < 0.0001) and asthma (p < 0.0001) than NIUA patients, showing similarities to NERD. These differences were not found in the sub-group of blended patients who developed such respiratory symptoms as glottis oedema; these were more similar to NIUA. The percentage of positive NPT-LASA was similar for blended (77%) and NERD groups (78.7%). We conclude that blended reactions are hypersensitivity reactions to NSAIDs affecting at least two organs. In addition to classical skin and respiratory involvement, in our population a number of patients also develop gastrointestinal symptoms. Given the high rate of positive responses to NPT-LASA in NERD as well as blended reactions, we suggest that all patients reporting respiratory symptoms, regardless of whether they have other associated symptoms, should be initially evaluated using NPT-LASA, which poses less risk than DPT.